Platelet‐rich plasma as a novel treatment for lichen planopillaris. Issue 4 (14th March 2016) - Bolanča, Željana; Goren, Andy; Getaldić‐Švarc, Biserka; Vučić, Majda; Šitum, Mirna
ABSTRACT: Treatment of lichen planopillaris (LPP) remains a significant challenge due to the irreversible damage inflicted on hair follicles combined with the low efficacy of existing treatments. We hypothesized that growth factors released by the use of platelet‐rich plasma (PRP) may arrest the development of LPP. To test our hypothesis, we treated an LPP patient that has failed previous treatments with a new PRP regimen. Following PRP treatment and six months follow‐up, the patient experienced complete regression of itching and hair shedding. To the best of our knowledge, this is the first report of successful treatment of LPP with a PRP regimen.